Factors that Influence Financial Statement Fraud with Fraud Pentagon Analysis - Danny Wibowo; Yusril Putra (Asia Pacific Fraud Journal, 2023)
This study has a purpose to observe what is the impact of Fraud Pentagon Theory. This includes the following opportunity (as proxied) using the industrial nature variables and ineffective monitoring, capability (as proxied by the variable of change in director), rationalization (as proxied by the variable of change in auditor), arrogance (as proxied by the variable of political connection), and pressure (as proxied by the variables of financial target and financial stability), toward financial statement fraud in an agricultural company listed on the Indonesia Stock Exchange (IDX) from 2016 - 2019, with a total sample of 72 agricultural firms. There are two kinds of quantitative approaches used in this study. First is a purposive sampling technique. Second, multiple linear regression using SPSS 24. This finding shows financial stability variables and targets cause financial statement fraud. Fortunately, those variables which not effect financial statement fraud are the industrial nature, ineffective monitoring, director changing, auditor changing, and political connection.